The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1042/bst20160083
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the ALK1 ligands, BMP9 and BMP10

Abstract: Bone morphogenetic protein (BMP)9 and BMP10 are high affinity ligands for activin receptor-like kinase 1 (ALK1), a type I BMP receptor mainly expressed on vascular endothelial cells (ECs). ALK1-mediated BMP9/BMP10 signalling pathways have emerged as essential in EC biology and in angiogenesis. Several genetic mutations in the genes encoding the ligands and receptors of this pathway have been reported in two cardiovascular diseases, pulmonary arterial hypertension (PAH) and hereditary haemorrhagic telangiectasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…TGF-b signaling at the BBB is facilitated by transmembrane serine-threonine kinase receptors [i.e., activin receptor-like kinase (ALK)-1 and ALK5]. ALK1 and ALK5 constitute the primary TGF-b receptors that mediate vascular remodeling and angiogenesis (Oh et al, 2000) and have been shown to induce opposite effects at the BBB (Lebrin et al, 2005;Ronaldson et al, 2009;Curado et al, 2014;Wei et al, 2014;Li et al, 2016). Effects of TGF-b/ALK1 signaling at the BBB can be studied using the well-characterized ALK1 receptor agonist bone morphogenetic protein 9 (BMP-9) (Brown et al, 2005;Herrera et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-b signaling at the BBB is facilitated by transmembrane serine-threonine kinase receptors [i.e., activin receptor-like kinase (ALK)-1 and ALK5]. ALK1 and ALK5 constitute the primary TGF-b receptors that mediate vascular remodeling and angiogenesis (Oh et al, 2000) and have been shown to induce opposite effects at the BBB (Lebrin et al, 2005;Ronaldson et al, 2009;Curado et al, 2014;Wei et al, 2014;Li et al, 2016). Effects of TGF-b/ALK1 signaling at the BBB can be studied using the well-characterized ALK1 receptor agonist bone morphogenetic protein 9 (BMP-9) (Brown et al, 2005;Herrera et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The proangiogenic effects of several members of this family are mediated via activin receptor-like kinase 1 (ALK1), a type I receptor [2], which has been shown to be essential for vascular development, remodeling and pathological angiogenesis. Although multiple BMPs can activate ALK1, BMP9 and BMP10 are specific activators in endothelial cells [3]. …”
Section: Introductionmentioning
confidence: 99%
“…BMPs are involved in many different biological activities, during both embryonic development and adult life, and control, in particular, the vascular system homeostasis . BMPs are dimeric polypeptides that are generally secreted in association with their processed precursor part, producing either active or latent complexes . BMPs transduce their biological signal from the cell surface through binding to two different types of serine/threonine kinase receptors (RI, also named activin receptor‐like kinase [ALK], and RII), subsequent phosphorylation of the intracellular transcription factor Smad1, Smad5, or Smad9, and translocation of these phospho‐Smads in complex with Smad4 to the nucleus, where they regulate the transcription of target genes.…”
mentioning
confidence: 99%